2016
DOI: 10.18632/oncotarget.10614
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter antagonists target tumor-initiating cells in a transgenic mouse model of breast cancer

Abstract: Accumulating data suggests that the initiation and progression of human breast tumors is fueled by a rare subpopulation of tumor cells, termed breast tumor-initiating cells (BTIC), which resist radiotherapy and chemotherapy. Consequently, therapies that abrogate BTIC activity are needed to achieve durable cures for breast cancer patients. To identify such therapies we used a sensitive assay to complete a high-throughput screen of small molecules, including approved drugs, with BTIC-rich mouse mammary tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 68 publications
2
48
0
Order By: Relevance
“…Interestingly, overexpressing cDNAs encoding the 5-HT 2C or 5-HT 2A receptors results in the transformation of mouse 3T3 fibroblasts demonstrating that they function as oncogenes in the focus-forming assay [ 55 , 56 ]. Consistent with our findings serotonergic system antagonists, including several that we independently discovered [ 17 ], were recently found to inhibit sphere formation by glioblastoma cell lines [ 57 ] and to affect the growth of tumor allografts and xenografts of neuroendocrine origin [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Interestingly, overexpressing cDNAs encoding the 5-HT 2C or 5-HT 2A receptors results in the transformation of mouse 3T3 fibroblasts demonstrating that they function as oncogenes in the focus-forming assay [ 55 , 56 ]. Consistent with our findings serotonergic system antagonists, including several that we independently discovered [ 17 ], were recently found to inhibit sphere formation by glioblastoma cell lines [ 57 ] and to affect the growth of tumor allografts and xenografts of neuroendocrine origin [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…We have shown that spheres arise from dispersed tumorsphere-derived cells in direct proportion to the number of cells plated into the medium, and that the frequency of sphere-forming cells, which averages 5% of the total tumor cell population in human breast tumor cell line-derived tumorspheres, can be accurately quantified over a range of cell densities [ 27 ]. Moreover plating single tumorsphere-derived cells into the wells of 96-well plates yields spheres at the same frequency as those forming when the cells are plated at higher cell densities [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations